2015
DOI: 10.1002/mnfr.201400863
|View full text |Cite
|
Sign up to set email alerts
|

Diet rich in high glucoraphanin broccoli reduces plasma LDL cholesterol: Evidence from randomised controlled trials

Abstract: ScopeCruciferous-rich diets have been associated with reduction in plasma LDL-cholesterol (LDL-C), which may be due to the action of isothiocyanates derived from glucosinolates that accumulate in these vegetables. This study tests the hypothesis that a diet rich in high glucoraphanin (HG) broccoli will reduce plasma LDL-C.Methods and resultsOne hundred and thirty volunteers were recruited to two independent double-blind, randomly allocated parallel dietary intervention studies, and were assigned to consume eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 50 publications
(69 reference statements)
3
51
1
Order By: Relevance
“…Recently it was shown that a broccoli diet could lower plasma LDL cholesterol in humans, suggesting that hepatic trafficking of lipids may be altered by broccoli (Armah et al, 2015). Our previous study using mice support this finding, showing decreased lipidosis by supplemental dietary broccoli in mice consuming a Westernized diet (Chen, Wallig, & Jeffery, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that a broccoli diet could lower plasma LDL cholesterol in humans, suggesting that hepatic trafficking of lipids may be altered by broccoli (Armah et al, 2015). Our previous study using mice support this finding, showing decreased lipidosis by supplemental dietary broccoli in mice consuming a Westernized diet (Chen, Wallig, & Jeffery, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sulforaphane also prevent cardiovascular diseases such as hypertension or atherosclerosis in rats prone to suffer spontaneous hypertensive strokes (Wu et al 2004;Senanayake et al 2012). In humans, Armah et al (2015) demonstrated that the dietary intake of broccoli with a high content in glucoraphanine resulted in a high decrease of LDL cholesterol, which is related with coronary diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It possesses both nourishing and healthcare functions. In addition, its edible parts are also rich in ascorbic acid, which can enhance the detoxification ability of liver and improve immunity; Polyphenols can effectively eliminate free radicals in the body, improve blood circulation, reduce cholesterol, inhibit low-density lipoprotein (LDL-C), cholesterol oxidation and so on [3][4][5]. Free radicals are harmful substances that are produced by oxidation.…”
Section: Introductionmentioning
confidence: 99%